MICROPLASTIC CHARACTERISTICS IN Amphibalanus amphitrite AS A POTENTIAL BIOINDICATOR IN THE WATERS AROUND THE SUROBOYO BRIDGE - Rheina Nurhaliza; Aunurohim Aunurohim; Dian Saptarini (Marine & Earth Science and Technology Research Center, DRPM, ITS, 2025)
Microplastics are small particles resulting from plastic degradation, typically ranging from 0.001 mm to less than 5 mm in size. This study aimed to determine the visual and polymer or chemical characteristics of microplastics found in barnacles Amphibalanus amphitrite collected from the waters surrounding the Suroboyo Bridge, as well as to evaluate their potential as a bioindicator species for microplastic pollution. A quantitative descriptive approach was applied, including visual identification of microplastics using a stereo microscope and chemical characterization using Attenuated Total Reflectance Fourier Transform Infrared (ATR-FTIR). Barnacle samples were categorized into two size groups, namely small and large, to examine the relationship between barnacle size and microplastic characteristics. The average shell size of the large group was 2.88 cm, while the small group averaged 1.24 cm. The results showed that the average abundance of microplastics in the soft tissues of large barnacles was 61.93 particles per individual, while small barnacles contained 26.3 particles per individual. The dominant visual characteristics of microplastics in both groups were fragment shapes, blue coloration, and particle sizes ranging from 10 to 50 µm. Polymer analysis identified polypropylene and nylon as the main polymer types. Furthermore, this study highlights a clear relationship between barnacle size and microplastic accumulation, where larger individuals tend to accumulate higher quantities of microplastics. However, the size distribution of microplastics, ranging from 10 to 50 µm, was relatively consistent across both barnacle size groups, indicating that particle size is not strongly influenced by barnacle size but rather by environmental availability. These findings support the potential of Amphibalanus amphitrite as a bioindicator species for microplastic pollution due to its sessile nature and filter-feeding mechanism, which enable the accumulation of microplastics over time.